The Fourth Industrial Revolution in South Africa’s basic education: a search for cogent curriculum justice - Sehlako, Nothando; Chibambo, Mackenzie Ishmael; Divala, Joseph Jinja (Frontiers in Education, 2023)
This study sought to examine how the Fourth Industrial Revolution (4IR) has promulgated curriculum (in) justices within basic education contexts in South Africa. Utilizing qualitative methods, we interviewed fifteen students and three teachers from three schools and one ICT district manager Johannesburg. We also deployed critical interpretivism to analyze the documents and the responses form the research subjects in order to explain how the ideologies related to use of 4IR and its roles in education helped create and sustain curriculum (in) justices in South Africa. We mainly used Ideal Utilitarianism by George Moore, Justice as Fairness by John Rawls, and the Technology Acceptance Model by Fred Davis as key theoretical frameworks for analyzing 4IR in education and social contexts. Key findings showed that 4IR has hugely sorted, stratified and unequalise rural-poor students more than the rich students especially at the basic education level. Essentially, the benefits highlighted by some respondents particularly teachers could not help offset the injustice and damage 4IR unleashed upon the marginalised groups of students at this level. While acknowledging that 4IR was irreversible at this point since it was now part of human life, we recommended that DBE should judiciously revisit the 4IR policy governing Operation Phakisa (OPI) education policy, by instituting different support systems that will ensure provision of an equitable and just 4IR aided education for everybody. One such supports, but not limited to that, was provision of consistent capacity building trainings for the schools and society.